Chronic cutaneous lichenoid graft‐versus‐host disease at the area of herpes zoster infection and at a vaccination site. (1st October 2015) - Palacios‐Alvarez, I.; Santos‐Briz, A.; Jorge‐Finnigan, C.; Cañueto, J; Fernandez‐López, E.; Roman‐Curto, C.
Summary: Cutaneous graft‐versus‐host disease (GVHD) is a frequent complication of allogeneic bone marrow transplant and haematopoietic cell transplantation, but it is rarely presented as a Wolf's isotopic response. We report a patient who developed chronic lichenoid GVHD following the dermatomes previously affected by varicella zoster virus (VZV) infection. Nineteen months later, the same patient suffered from reactivation of GVHD at the injection site of an influenza vaccination. We review the literature concerning GVHD appearing after VZV infection and discuss the possible implications of this case and the pathogenic hypotheses.